Kebutuhan Pengembangan Profesional Guru TK Dalam Sistem Perlindungan Anak di Sekolah - Mutiara Magta; Nurbiana Dhieni; Sri Wulan (Jurnal Ilmiah POTENSIA, 2026)
Kindergarten (TK) teachers hold a strategic position in the child protection system due to their intensive daily interactions with young children. This study aims to describe the professional development needs of kindergarten teachers in the field of child protection. This study used a survey research method involving 82 kindergarten teachers spread across the provinces of Jakarta and West Java as respondents. Data collection was conducted using a Likert-scale questionnaire distributed using G-form. The analysis results showed that all three dimensions of need were in the highly needed category: the knowledge dimension obtained the highest mean (M=3.61), followed by the skills dimension (M=3.55), and the professional development support dimension (M=3.51). Overall, more than 93% of respondents stated that they strongly needed capacity building in all aspects measured. The item with the highest score was recognizing signs of violence and neglect (M=3.65), while incident documentation received the lowest score but was still highly needed (M=3.41). These findings emphasize the urgency of a structured, sustainable professional development program that is based on the real needs of PAUD teachers in the field, particularly in the field of child protection.